RNA Sequence, Structure, and Function: Computational and Bioinformatic Methods - Gorodkin, Jan.; Ruzzo, Walter L.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
The existence of genes for RNA molecules not coding for proteins (ncRNAs) has been recognized since the 1950's, but until recently, aside from the critically important ribosomal and transfer RNA genes, most focus has been on protein coding genes.  However, a long series of striking discoveries, from RNA's ability to carry out catalytic function, to discovery of riboswitches, microRNAs and other ribo-regulators performing critical tasks in essentially all living organisms, has created a burgeoning interest in this primordial component of the biosphere.  However, the structural characteristics and evolutionary constraints on RNA molecules are very different from those of proteins, necessitating development of a completely new suite of informatic tools to address these challenges. In RNA Sequence, Structure, Function: Computational and Bioinformatic Methods, expert researchers in the field describe a substantial and relevant fraction of these methodologies from both practical and computational/algorithmic perspectives. Focusing on both of these directions addresses both the biologist interested in knowing more about RNA bioinformatics as well as the bioinformaticist interested in more detailed aspects of the algorithms.  Written in the highly successful Methods in Molecular Biology series format, the chapters include the kind of detailed description and implementation advice that is crucial for getting optimal results.  Thorough and intuitive, RNA Sequence, Structure, Function: Computational and Bioinformatic Methods aids scientists in continuing to study key methods and principles of RNA bioinformatics.
Concepts and Introduction to RNA Bioinformatics -- The Principles of RNA Structure Architecture -- The Determination of RNA Folding Nearest Neighbor Parameters -- Energy Directed RNA Structure Prediction -- Introduction to Stochastic Context Free Grammars -- An Introduction to RNA Databases -- Energy-based RNA Consensus Secondary Structure Prediction in Multiple Sequence Alignments -- SCFGs in RNA Secondary Structure Prediction: A Hands-on Approach -- Annotating Functional RNAs in Genomes using Infernal -- Class-specific Prediction of ncRNAs -- Abstract Shape Analysis of RNA -- Introduction to RNA Secondary Structure Comparison -- RNA Structural Alignments, Part I: Sankoff Based Approaches for Structural Alignments -- RNA Structural Alignments, Part II: Non-Sankoff Approaches for Structural Alignments -- De novo Discovery of Structured ncRNA Motifs in Genomic Sequences.,- Phylogeny and Evolution of RNA Structure -- The Art of Editing RNA Structural Alignments -- Automated Modeling of RNA 3D Structure -- Computational Prediction of RNA-RNA Interactions -- Computational Prediction of microRNA Genes -- MicroRNA Target Finding by Comparative Genomics -- Bioinformatics of siRNA Design -- RNA-protein Interactions: An Overview.
Keywords: Bioinformatics; Human genetics; Bioinformatics; Human Genetics